Penerapan Sistem Digitalisasi Teknologi Informasi dalam Pengelolaan serta Promosi Potensi Desa Bayem Melalui Matic - Rezza Fahlevvi, Mohammad; Maulana, Achmat (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
Bayem Village, located in Kasembon Subdistrict, Malang Regency, possesses rich natural and cultural potential that is highly promising for tourism development. However, the promotion and management of these resources remain suboptimal, thus limiting their contribution to the local community’s welfare. This community service program aims to optimise the use of the MATIC platform (Malang Regency Tourism Intelligence Centre) as a digital and data-driven tool for promoting and managing tourism destinations in Bayem Village. The activities are carried out through training sessions for residents and tourism managers, covering skills such as tourism data management, creative promotional content creation, and digital marketing strategies to attract more visitors. Additionally, the program includes the formulation of data-based promotional strategies, updating of tourism information on the MATIC platform, and ongoing technical assistance. Through the utilisation of this information technology, it is expected that there will be an increase in tourist visits, strengthening of community capacity in tourism management, and the realisation of sustainable destination management in Bayem Village.